Peranan Media Online ”Tanoshiijapanese.com” Sebagai Solusi Pembelajaran Kanji di Masa Pandemi - Kun Makhsusy Permatasari; Alo Karyati (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2020)
The COVID-19 pandemic has changed all of our activities and lifestyles. Work, study, socializing and all activities related to physical contact all change. This includes teaching and learning activities. The teaching and learning activities that we have been doing in the classroom, during this pandemic, require all activities to be carried out from home. This automatically changes the habits of both the teacher and the students being taught. The Covid-19 pandemic is not only happening in Indonesia, but is evenly distributed throughout the world. Therefore, there needs to be media that can be used as a means for teaching and learning activities during this pandemic. Based on this, the researchers tried to use online media